PENGGUNAAN KERTAS ORIGAMI UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI BANGUN DATAR SISWA KELAS III SD - Farulyan, Neska; Rahmawati, Siti; Alfiqri, M.pr; Saputra, Dika; Kharanza, Yoenua; Rohani, Siti; Hopeman, Teofilus Ardian (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The study aims to determine the effectiveness of using origami paper in improving the learning achievement of grade III elementary school students. The research method used is classroom action research (CAR) which is carried out in two cycles. Data collection is carried out through observation sheets and comprehension tests. The results of the study found that although the average academic achievement of students in the "very good" category in cycle I with an average of 80.9, there were still 10 students who were not fully academically capable. After improvements were made in cycle II, the average score of students in the special category increased significantly to 93.1 with all students achieving completion. Based on the results of the study, it was concluded that the use of origami as a learning medium effectively improves the learning outcomes of Mathematics in flat geometry material for grade III students. Origami media can express abstract Mathematical concepts so that they are easier for students to understand. In addition, the use of origami supports increases student involvement and enthusiasm in learning.